2012
DOI: 10.1371/journal.pone.0030237
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for the Association between the Early Growth Response 3 (EGR3) Gene and Schizophrenia

Abstract: Recently, two genome scan meta-analysis studies have found strong evidence for the association of loci on chromosome 8p with schizophrenia. The early growth response 3 (EGR3) gene located in chromosome 8p21.3 was also found to be involved in the etiology of schizophrenia. However, subsequent studies failed to replicate this finding. To investigate the genetic role of EGR3 in Chinese patients, we genotyped four SNPs (average interval ∼2.3 kb) in the chromosome region of EGR3 in 470 Chinese schizophrenia patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 62 publications
(98 reference statements)
3
23
0
Order By: Relevance
“…36 Human genetic studies further support a role for EGR3 in this mental illness, as variations in the EGR3 gene have been associated with schizophrenia in three populations. 1921 Post-mortem studies have also shown decreased levels of EGR3 expression in the brains of schizophrenia patients. 20, 37 Animal studies show that mice lacking Egr3 display schizophrenia-like abnormal behaviors, such as increased locomotion, aggression and deficits in memory and synaptic plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…36 Human genetic studies further support a role for EGR3 in this mental illness, as variations in the EGR3 gene have been associated with schizophrenia in three populations. 1921 Post-mortem studies have also shown decreased levels of EGR3 expression in the brains of schizophrenia patients. 20, 37 Animal studies show that mice lacking Egr3 display schizophrenia-like abnormal behaviors, such as increased locomotion, aggression and deficits in memory and synaptic plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…Such disrupted genes were relevant to neurological diseases, including systemic lupus erythematosus (SLE; table 4). Xbp1 and Egr3 have been previously associated with schizophrenia given their roles in unfolded protein response in neurons and in neuromuscular synaptic transmission, respectively [47,48]. A number of genes were also involved in endoplasmic reticulum (ER) stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Another gene that has been implicated in both SZ and circadian organization is immediate early gene growth response 3 (Egr3) 162,[165][166][167][168] . Additional support for this candidate gene is provided by Egr3-deficient mice (−/−), which display behaviors that are reminiscent of SZ and sleep less than WT controls, even though the circadian organization of the sleep-wake cycle remained intact 169 .…”
Section: Circadian Rhythm Disruption and Schizophreniamentioning
confidence: 99%